Setting – based prevalence and correlates of central obesity: findings from a cross-sectional study among formal sector employees in Dodoma City, Central Tanzania - Munyogwa, Mariam John (BMC Public Health, 2021)
BACKGROUND: Obesity at the workplace has been associated with symptoms of lower self-esteem, increased individual and employer healthcare costs, increased absenteeism and presenteeism and reduced productivity. Therefore, this study was designed to study the prevalence and correlates of central obesity among formal sector employees in Dodoma City. METHODS: Study design was a cross-sectional survey conducted from March to June, 2019. Participants were employees from formal sector employment defined as those paid regular monthly wage and with either a secured permanent or temporary contract. Simple random sampling was used to select four out of fifteen large buildings hosting various establishments. Respondents were obtained conveniently and interviewed face to face. Central obesity was defined as a waist circumference greater than 102 cm for males and greater than 88 cm for females. Chi-square test was conducted to assess the differences among the groups. Simple and multiple logistic regression models were fitted to identify the correlates of central obesity. RESULTS: A total of 392 respondents (98% response rate) agreed and participated in the study. The overall prevalence of central obesity was found to be 41.8% (164/392). The prevalence of central obesity was significantly higher among females (67.4% p < 0.001), respondents aged ≥51 years (60%, p = < 0.001), administrators (55.1% p = < 0.05), respondents with salary of > 1,000,000 Tanzanian Shilling (TSh.) per month (54.4%, p = < 0.05), respondents who eat homemade meals at the workplace (64.2%, p = < 0.05) and respondents with hypertension (62.5%, p = < 0.05). Correlates of central obesity were found to be female sex (AOR = 9.53; 95% CI: 5.49, 16.78), increased age, eating homemade meals at the workplace (AOR = 2.32; 95% CI: 1.04, 4.19) and hypertension (AOR = 3.15; 95% CI: 1.41, 6.91). CONCLUSIONS: The present study revealed high prevalence of central obesity among formal sector employees in Dodoma City. Scholars and stakeholders are urged to generate more evidences and design appropriate interventions to curb the situation. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12889-020-10142-4.